The arctiidae and sphingidae (Lepidoptera: Heterocera) of Machu Picchu historical Sanctuary, Cuzco, Perú: A preliminar survery - Grados, Juan (2002)
A list of 80 species of Arctiidae and 17 of Sphingidae recorded until now at the Machu Picchu Historical Sanctuary, Cuzco, Perú, is presented herein, indicating their altitudinal distribution.